Exercise to transform tumours from cold to hot and improve immunotherapy responsiveness - Hapuarachi, Brindley; Danson, Sarah; Wadsley, Jon; Muthana, Munitta (Frontiers in Immunology, 2023)
Exercise provides significant health benefits to patients diagnosed with cancer including improveding survival outcomes, quality of life and reduciedng cancer recurrence. Across multiple murine cancer models, aerobic exercise and resistance training has exhibited anti-tumour properties illustrated by inhibited tumour growth, reduced metastatic potential and modulation of the tumour microenvironment to allow the recognition and destruction of cancer cells. Clinical studies have demonstrated tThe rapid mobilisation and circulatory release of mature lymphoid populations, myokines and cytokines occurs with exercise along with tumour vasculature normalisation. Tumour microenvironments enriched with immune cells with anti-cancer potential, such as CD8+ T cells, are termed 'hot', whilst those favouring an immunosuppressive environment and lacking in effector immune cells are would be classed as 'cold'. Pre-clinical evidence suggests Eexercise training has the potential to reprogramme cold tumours to become hot, although this requires validation in clinical studies. This hot environment wcould potentiate immunotherapy responsiveness, improving survival outcomes of patients undergoing cancer immunotherapy and allow those with typically cold tumours to benefit from immunotherapy.This review discusses the complex interactions between exercise and cancer, including exercise-induced alterations within the tumour microenvironment and systemic immunity. The potential role exercise may play in improving cancer immunotherapy responsiveness is explored. This review also highlights the need for translational studies exploring the role of exercise in patients with cancer with the potential to widen the spectrum of tumours that derive significant benefit from immunotherapy.